Report on proposed upgrading and new interior design scheme of Saba’ Restaurant for Al-Qodwah Sdn Bhd at 4800 Suite, 0-2. Ground Floor, Block A1 Jalan Perdana, Cbd Perdana, 6300 Cyberjaya, Selangor / Mohamad Al-Aedil Mohamad Ramsi - Mohamad Ramsi, Mohamad Al-Aedil (Faculty of Architecture, Planning and Surveying, 2009)
Proposed Upgrading and New Interior Design Scheme of Saba’ Restaurant for Al-Qodwah Sdn. Bhd. Is proposed for a new image to its interior and to appeal the corporate image. Recently the restaurant is starling to grow in this Food and Beverages business. Therefore the upgrading needs to occur to make it easier for the customers to have an impression of an Arabian Yemen Restaurant and also to offer comfort to the customers. The concept has to relate to Yemen therefore it can communicate directly to the customers. The interior flow has to be proper in its organization so that the staff and customer circulation is divided. By executing this project, the client hopes to bring in tourists and even Malaysians to come to Cyberjaya so that they can experience the Yemen environment and culture.